If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(2)+3y=13
We move all terms to the left:
-7(2)+3y-(13)=0
We add all the numbers together, and all the variables
3y-85=0
We move all terms containing y to the left, all other terms to the right
3y=85
y=85/3
y=28+1/3
| a+6+17/a=9 | | (2+2)x(8-4)=x | | g3/5−1/3=−10/3 | | 2x+10+33=x+5 | | 10=x/2x2/1 | | 10+4x=-2x=26 | | 4x^2+3x-5=2x+7 | | 7x+1=12x-25 | | a/19+3=8 | | -5x+10=4x-17 | | D=24x2 | | 4y=56;y=14 | | 7(8)+7y=-7 | | 12+f=-6 | | 4x+x•x=165 | | 3/5(5x+1)=-3x | | -46=x-90 | | 6p^2-64p-120=0 | | 45=-5y-4y | | f=8f−7f | | x-70=35 | | 8x-20=368x-20+20=368x=36 | | 5x+8(-4)=-12 | | 4+x6=-7 | | 4t=6t-6 | | -24=4(4x+)-4(8+x) | | -9-10=-10+9u | | 8−2k=k−10 | | 10y+2=10y+5 | | √2x-4=-x | | 40^2-30x=135 | | 2(-8f+7)=5+9(-3f-10) |